2014
DOI: 10.1111/nph.13218
|View full text |Cite
|
Sign up to set email alerts
|

GLABROUS INFLORESCENCE STEMS3 (GIS3) regulates trichome initiation and development in Arabidopsis

Abstract: SummaryArabidopsis trichome formation is an excellent model for studying various aspects of plant cell development and cell differentiation. Our previous works have demonstrated that several C2H2 zinc finger proteins, including GIS, GIS2, ZFP5, ZFP6 and ZFP8, control trichome cell development through GA and cytokinin signalling in Arabidopsis.We identified a novel C2H2 zinc finger protein, GLABROUS INFLORESCENCE STEMS 3 (GIS3), which is a key factor in regulating trichome development in Arabidopsis.In comparis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
81
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(82 citation statements)
references
References 41 publications
(78 reference statements)
1
81
0
Order By: Relevance
“…So far, all the other identified trichome formationregulating transcription factors, including the C2H2 transcription factors GIS, GIS2, and GIS3, the ZINC FINGER transcription factors ZFP5, ZFP6, and ZFP8, and the miR156-directed transcription factor SPL9, are reported to function through the regulation of, directly or indirectly, the expression of the key transcription factor genes in the trichome formation pathway (Gan et al, 2006(Gan et al, , 2007Yu et al, 2010;Zhou et al, 2011Zhou et al, , 2013Sun et al, 2015). Our experimental data suggest that this is also the case with NTL8.…”
Section: Mechanism For the Action Of Ntl8 In The Regulation Of Trichomentioning
confidence: 55%
See 3 more Smart Citations
“…So far, all the other identified trichome formationregulating transcription factors, including the C2H2 transcription factors GIS, GIS2, and GIS3, the ZINC FINGER transcription factors ZFP5, ZFP6, and ZFP8, and the miR156-directed transcription factor SPL9, are reported to function through the regulation of, directly or indirectly, the expression of the key transcription factor genes in the trichome formation pathway (Gan et al, 2006(Gan et al, , 2007Yu et al, 2010;Zhou et al, 2011Zhou et al, , 2013Sun et al, 2015). Our experimental data suggest that this is also the case with NTL8.…”
Section: Mechanism For the Action Of Ntl8 In The Regulation Of Trichomentioning
confidence: 55%
“…Data represent the mean 6 SD of 18 plants. Yu et al, 2010;Zhou et al, 2011Zhou et al, , 2013Sun et al, 2015). To examine if this is the case for NTL8, we tested, by using qRT-PCR, the expression of the MBW complex component genes TTG1, GL1, GL3, and EGL3, and their target genes GL2 and singlerepeat R3 MYB genes TRY, CPC, ETC1, ETC2, ETC3, TCL1, and TCL2 in the ntl8-1D mutant seedlings.…”
Section: Trichome Formation In the Ntl8 Mutants Is Largely Unaffectedmentioning
confidence: 99%
See 2 more Smart Citations
“…The relative expression of the transcript levels of trichome-related genes was calculated by △CT method (Livak & Schmittgen, 2001) after being normalized to the internal control of gene encoding actin (ACTIN2). The primers for the genes were designed according to Tominaga-Wada et al (2013) and Sun et al (2015) which were shown in Supplemental Table 2.…”
Section: End-point Semi-quantitative and Real-time Rt-pcrmentioning
confidence: 99%